A New Paradigm for Learning Chemistry: A Virtual-Contextual Experimental Model for Students with Numeration Deficit - Yosephine Debbie Damayanti; Rinda Anggita Putri (Department of Chemistry, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang, 2025)
This study aimed to examine the effectiveness of a visual–numeracy learning approach in improving chemistry education students’ understanding of atomic structure and electron configuration. A quasi-experimental method with a pretest–posttest design was employed. The participants consisted of 42 first-semester students enrolled at a state university. The visual–numeracy approach was implemented through the integration of orbital diagrams, three-dimensional atomic models, infographics, and interactive numerical exercises designed to support conceptual and analytical reasoning. The results demonstrated a substantial improvement in students’ learning outcomes, as reflected in the increase in the mean score from 48.7 on the pretest to 84.2 on the posttest. In addition to quantitative gains, students showed enhanced analytical abilities, particularly in explaining anomalous electron configurations in transition elements and in relating electron configurations to periodic trends and physicochemical properties of elements. Student engagement and active participation in discussions and learning tasks also increased markedly, rising from 36% to 85%. These findings indicate that the visual–numeracy approach positively influences not only cognitive learning outcomes but also affective and psychomotor aspects of student learning. By enabling students to visualize abstract concepts and apply numerical reasoning simultaneously, this approach fosters deeper conceptual understanding and more meaningful learning experiences. Therefore, the visual–numeracy approach is highly suitable for broader integration into introductory chemistry courses, especially for topics that require strong spatial visualization and logical–mathematical reasoning